Global patterns and health impact of unintentional injuries among children and adolescents, 1990–2021 - Wei, Wei; Lyu, Wei; Zhang, Yuchen (Frontiers in Public Health, 2025)
SummaryUnintentional injuries significantly threaten the health of children and adolescents globally. Annually, injuries result in approximately five million deaths worldwide, with around 12% occurring in children. This study investigates global trends in incidence, mortality, and disability-adjusted life years (DALYs) associated with unintentional injuries among children and adolescents from 1990 to 2021.MethodsWe conducted an analysis of global unintentional injury incidence, mortality, and DALYs among individuals aged 0–19 years using data from the Global Burden of Disease (GBD) database. Incidence, mortality, and DALY rates per 100,000 population were calculated, accompanied by 95% uncertainty intervals (UI). Data from 204 countries and territories were stratified by age, sex, and geographic region. Trend analyses utilized Joinpoint regression modeling to calculate annual percentage changes (APC) and log-transformed linear regression to estimate the estimated annual percentage change (EAPC). Projections of injury burden through 2035 were generated using Bayesian age-period-cohort (BAPC) modeling.FindingsGlobally, in 2021, unintentional injuries in children and adolescents resulted in 157,808,979 cases (95% UI: 138,280,367–179,472,942), 305,596 deaths (95% UI: 240,004–365,146), and 28,410,167 DALYs (95% UI: 23,100,433–33,513,238). Among the five socio-demographic index (SDI) regions, the low-middle SDI region exhibited the most significant decrease in injury incidence. Regionally, from 1990 to 2021, the Caribbean experienced the largest relative increase in injury incidence (EAPC 0.25, 95% CI: −0.60 to 1.11). At the country level, India reported the highest absolute number of cases (24,115,574; 95% UI: 21,137,414–27,296,091). BAPC modeling predicts a continued reduction in the global burden of unintentional injuries up to 2035.InterpretationGlobal trends demonstrate declining incidence, mortality, and DALYs associated with unintentional injuries among children and adolescents. Comprehensive epidemiological insights are critical for enhancing targeted prevention strategies and control measures to mitigate injury burden in this vulnerable population.